Max & Ruby. Perfect pumpkin - Nickelodeon (Firm); Nelvana International (Firm); Paramount Home Entertainment (Firm) (Hollywood, Calif. : Paramount Home Entertainment, 2008)
Ruby and her little brother Max look for the perfect pumpkin for Halloween, and find that in order to make a great Jack o' Lantern, they have to work together!
Full screen.
Based on the characters created by Rosemary Wells.
Not rated.
DVD; Dolby Digital, stereo., NTSC.
Closed-captioned.
Keywords: Max (Fictitious character : Wells) -- Juvenile films; Ruby (Fictitious character : Wells) -- Juvenile films; Halloween -- Juvenile films; Pumpkin -- Juvenile films; Brothers and sisters -- Juvenile films; Animated television programs; Television programs for children; Video recordings for the hearing impaired